DISCLOSURE OF SUSTAINABLE DEVELOPMENT RESULTS BY CERTIFIED PORTUGUESE ORGANIZATIONS IN QUALITY, ENVIRONMENTAL, AND OCCUPATIONAL HEALTH AND SAFETY - Filipe Carvalho; Luis Fonseca; Gilberto Santos (International Journal for Quality Research)
Integrated Management System (IMS) supported by Management Systems Standards (MSSs) of the International Organization for Standardization (ISO), such as quality (ISO 9001), environmental (ISO 14001), and occupational health and safety (ISO 45001), is an important tool for approach the Sustainable Development (SD) in the organizations. Thus, the purpose of this research is twofold. First, it aims to qualify and quantify all the SD results (SDRs), that is, the Economic, Environmental, and Social (EES) results, which are disclosed to interested parties by the top management of 235 certified Portuguese organizations in Quality, Environmental, and Occupational Health and Safety (QEOHS). Second, it seeks to determine the profile of the organizations (QEOHS) in which the disclosure of SDRs (i.e., EES results) is more prominent. The research methodology was based on applying the content analysis method to qualify and quantify the disclosure of SDRs in institutional reports published on the institutional website. Holistically, the obtained results were grounded and commented on the theoretical assumptions that support the organizational theories (i.e., stakeholder theory, legitimacy theory, institutional theory, and resource-based view theory).